Pengembangan Strategi E-Commerce untuk UMKM Songket Khas Minangkabau: Analisis 4D yang Mendalam dan Komprehensif - 'Aini Koto, Nurul; Annas, Firdaus; Putri, Putri (Yayasan Lembaga Studi Makwa, 2023)
The development of an e-commerse strategy for Minangkabau songket businesses is crucial in the face of evolving market dynamics. The background of this research focuses on the challenges faced by songket businesses in effectively marketing their products in the digital era. With the increasing use of the internet and e-commerce, songket businesses need to adapt to remain relevant and competitive. This research uses Research and Developmen (R&D), with the Define, Design, Develop, Dissamble (4D) research method. The purpose of this research is to conduct an in-depth SWOT analysis to identify the strengths, weaknesses, opportunities, and threats faced by songket businesses in developing e-commerse strategies. The method used in this research is a comprehensive 4D analysis, with data collection through direct interviews with MSME owners in depth with MSME business actors. The interview results show that the main strengths of songket businesses lie in the quality of the products and the uniqueness of the designs that reflect Minangkabau culture. However, weaknesses such as lack of knowledge about digital marketing and limited market access are significant challenges. Opportunities to increase sales through e-commerce platforms and social media are huge, while threats from competition of similar products and changing consumer preferences need to be watched out for.